High-fidelity self-assembly pathways for hydrogen-bonding molecular semiconductors - Lin, Xu (Sci Rep, 2017)
The design of molecular systems with high-fidelity self-assembly pathways that include several levels of hierarchy is of primary importance for the understanding of structure-function relationships, as well as for controlling the functionality of organic materials. Reported herein is a high-fidelity self-assembly system that comprises two hydrogen-bonding molecular semiconductors with regioisomerically attached short alkyl chains. Despite the availability of both discrete cyclic and polymeric linear hydrogen-bonding motifs, the two regioisomers select one of the two motifs in homogeneous solution as well as at the 2D-confined liquid-solid interface. This selectivity arises from the high directionality of the involved hydrogen-bonding interactions, which renders rerouting to other self-assembly pathways difficult. In thin films and in the bulk, the resulting hydrogen-bonded assemblies further organize into the expected columnar and lamellar higher-order architectures via solution processing. The contrasting organized structures of these regioisomers are reflected in their notably different miscibility with soluble fullerene derivatives in the solid state. Thus, electron donor-acceptor blend films deliver a distinctly different photovoltaic performance, despite their virtually identical intrinsic optoelectronic properties. Currently, we attribute this high-fidelity control via self-assembly pathways to the molecular design of these supramolecular semiconductors, which lacks structure-determining long aliphatic chains.